Studies on the Plasmon-Induced Photoexcitation Processes of Molecules on Metal Surfaces - Nagasawa, Fumika; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This thesis proposes a novel way to catch light energy using an ultrasmall nanostructure. The author has developed photon-materials systems to open the way for novel photoexcitation processes based on the findings obtained from in-situ observation of the systems in which localized surface plasmon (LSP) and molecules interact strongly. The highly ordered metal nanostructure provided the opportunity for anisotropic photoexcitation of materials in an eccentric way. The optimization of the systems via nanostructuring and electrochemical potential control resulted in the novel excitation process using LSP to realize the additional transition for photoexcitation. Furthermore, excited electronic states formed the strong coupling between LSP and excitons of molecules. This thesis will provide readers with an idea for achieving very effective processes for photon absorption, scattering, and emission beyond the present limits of photodevices. .
General Introduction -- The Depolarisation Behaviour of Surface-Enhanced Raman Scattering Photons in a Metal Nanodimer Structure -- Simultaneous Measurement of Surface-enhanced Raman Scattering and Conductance using Mechanically Controllable Break Junction Technique -- Electronic Excitation of an Isolated Single-walled Carbon Nanotube by Tuning Electrochemical Potential -- Raman Enhancement via Polariton States Produced by Strong Coupling between Localised Surface Plasmons and Dye Excitons in Metal Nanodimers -- Electrochemical Control of Strong Coupling between Localised Surface Plasmons and Dye Excitons.
Keywords: Physical chemistry; Nanotechnology; Atoms; Molecules; Physical Chemistry; Nanotechnology; Atomic, Molecular and Chemical Physics